Analysis of returnee association websites: architecture and navigability - Korres, Oihane (2023)
[Objective] This investigation analyzed the attributes of architecture and navigability of web sites intended to provide information to Spanish returnees. [Methodology] This is an exploratory empirical study which uses a qualitative design with a statistical-descriptive basis, and makes use of absolute and relative frequencies. The qualitative analysis was carried out by means of a manual examination supported by the Atlas.Ti tool, guided by a theoretical model with empirical foundations. Data from 16 websites related to associations and federations of Spanish returnees active during the years 2019-2021 were analyzed. [Results] The websites analyzed were similar in terms of structure, interface and navigability. They use formats similar to those of current blogs, but their content was infrequently updated. They contain large amounts of information structured using hyperlink formats or attached documentation. [Conclusions] It is concluded that the architecture and navigability of web pages of Spanish associations and federations of returnees are much more notable for their similarities than for their differences. The investigation opens the way for further comparative and relational studies that will allow analysis of similarities and differences between websites, as well as the characterization of their communicative structures.